Risk and Complications of Rhinoplasty - Sahibzada Fawad Khan, Sayyed Muddasir Shah, Mubashar Ullah Jan, Haider Zaman, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the associated risk and complications of rhinoplasty. Study design: Prospective study Place and duration of study: ENT Department, Nowshera Medical College, Qazi Hussain Ahmad Medical Complex, Nowshera from 1st July 2021 to 30th June 2022. Methodology: One hundred cases suffering from nose deformation or required cosmetic alterations were included for rhinoplasty procedure. An open procedure for rhinoplasty was adapted with inside sutures. Nose reduction or cartilage grafting (n=58), conchal cartilage grafting (n= 29) and rib cartilage procedure (n=13) was performed as per requirement of the case for nose reshaping. Septum was deviated, straightened and nose projection was reduced for facilitation of breathing depending upon each patient’s individual requirements. Any types of complications observed were recorded and treated immediately. Results: Only 19% males underwent rhinoplasty procedure. The mean age of the cases was 34.5±12.62 years. The body mass index (BMI) mean value was 23.15±3.15kg/m2 with 22 such cases which were suffering from obesity. There were 37% cases who suffered from rhinoplasty related complications. Thirty percent of the patients suffered from functional deformities and required this procedure and 44% of cases which adapted rhinoplasty surgery due to both aesthetic as well as functional reasoning. Thirty-three percent of the patients were suffered from hematoma while 25% suffered from surgical site infection. Conclusion: Most of the patient suffered from hematoma followed by surgical site infection, pulmonary infection and deep vein thrombosis. Keywords: Aesthetic, Incidence, Cartilage, Breathing, Numbness